The way insoluble fiber incorporated in the diet changes its physiological response - Hartini, S.; Rahardjo, D. D.; Sasongko, H. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
The physiological effect of insoluble fibers may change with diet composition. The present study aimed to determine the difference in the physiological responses of broiler chickens fed diet incorporated with rice hulls in different ways. Two hundred and forty broiler chicks at two-days old were randomly placed in 30 cages and fed: control diet (based on corn-soybean) (CO), rice hull supplementation diet (CO + 4% of rice hulls) (RS), and rice hull inclusion diet (inclusion of 4% rice hulls in diet) (RI). The significant effects were mostly found in the starter phase. The RI increased ADG (P<0.05) but reduced empty ceca weight (P<0.05) in comparison to CO and RS. The RS increased the jejunal crypt depth (P<0.05) and reduced the small intestinal content (P<0.05). Birds fed RS and RI had higher villus height (P<0.05) and thicker jejunal mucosa (P<0.05) than those fed the CO. In the finisher phase, birds fed the RS had the narrower width of the upper and lower jejunal villi than the others. Supplementation or inclusion of insoluble fiber in the diet will lead to different physiological responses due to changes in diet composition.